HUBUNGAN PENGETAHUAN PERSONAL HYGIENE DENGAN KEJADIAN FLOUR ALBUS PADA MAHASISWI STIKES BAITUL HIKMAH - Yunitasari, Eva; Fitri, Feni Elda; Azizah, Salsabila Afifatul (Journal of Maternity Care and Reproductive Health, 2024)
Flour albus / leucorrhea is a condition where the vagina secretes mucus or fluid caused by germs. The main factor causing vaginal discharge is not maintaining good personal hygiene. Good personal hygiene can avoid a person from parasitic germs and viruses. The behavior of female students in overcoming vaginal discharge based on the pre-survey is by cleaning the female area and changing underwear without knowing how the characteristics of choosing good underwear. The purpose of the study was to determine the relationship between personal hygiene knowledge and the incidence of flour albus in female students of STIKes Baitul Hikmah. Type of quantitative research cross-sectional design with a population of 61 all female students level I and level II. The sampling technique used total sampling. The analysis test uses chi-square. The results of the study obtained a p-value = 0.002, which means that there is a significant relationship between personal hygiene knowledge and the incidence of flour albus in female students of STIKes Baitul Hikmah. Students are expected to apply good personal hygiene methods in everyday life and gain insight into the long-term effects of improper personal hygiene. This study can be a reference material for further researchers on personal hygiene knowledge with the incidence of flour albus.